(untitled) - Greer, Roger C. (Santa Barbara, California, 2013)
This comprehensive book prepares readers for a changing profession in the library and information field, presenting a holistic approach that examines theories and models and utilizes creative problem-solving strategies
Keywords: Information services,Dịch vụ thông tin